Analysis Of The Application Of Electronic Medical Record In RUMKITAL Dr. Mintohardjo With The Measures Of Effectiveness Method - Widjanarko, Sigit; Wandawa, Ganesa; Indarti, Agnes (Journal of Ageing And Family, 2022)
The phenomenon of the industrial revolution 4.0 accompanied by the rapid development of information technology has had a positive impact on the development of hospital management information systems. Currently, manual medical records are deemed no longer effective in relation to the community's need for quality, fast, precise, accurate and complete health services. Electronic Medical Record enables service providers to track patient data more quickly, identify visits, prevent and screen, help diagnose and manage disease so as to improve the quality of health services. This research was conducted to measure the effectiveness of the application of the Electronic Medical Record in Rumkital Dr. Mintohardjo by measuring the data input component, data integration and data security is assessed from the Usability, Flexibility and Efficiency of each component. Data collection was obtained from interviews and questionnaires from informants and respondents, namely officials and health workers at Dr. Rumkital. Mintohardjo regarding the application of Electronic Medical Records. The data obtained were then processed using the Measures of Effectiveness (MoE) method to measure the effectiveness of the application of the Electronic Medical Record. The hypothesis of this research is that the more effective the application of the Electronic Medical Record, the higher the quality of health services at Dr. Hospital. Mintohardjo and proven through data processing using the Measures of Effectiveness method. This study found the results that the effectiveness of the application of the Electronic Medical Record in Rumkital Dr. Mintohardjo has an MoE value of 0.676, it is included in the effective category. Keywords Electronic Medical Record, Measures Of Effectiveness, Rumkital Dr Mintoharjo